Honeycomb porous N-doped carbon synergized with ultrafine Ni2P electrocatalyst for boosting polysulfide conversion in lithium–sulfur batteries. (20th March 2023) - Zhang, Heng; An, Yafei; Li, Shiwen; Li, Zhaolei; Geng, Dongxiang; Sha, Dawei; Pan, Long; Qiu, Guanglin; Yan, Chao
Highlights: Ultrafine Ni2 P nanodots decorated porous N-doped carbon was fabricated by a facile chelate-phosphating strategy. Ni2 P electrocatalysts effectively enhanced chemisorption, accelerated LiPS conversion, and regulated Li2 S precipitation. The Li–S cell with Ni2 P@PNC/S cathode under lean electrolyte system achieved outstanding electrochemical performance. Abstract: The intractable shuttle effect and sluggish redox kinetics are major impediments to the practical application of lithium–sulfur (Li–S) batteries. Herein, ultrafine Ni2 P nanodots decorated porous N-doped carbon (Ni2 P@PNC) is successfully constructed by a novel chelate-phosphating strategy and employed as sulfur host to realize effective suppression of shuttle effect and enhancement of redox kinetics. Owing to the strong polarity and catalytic activity, the Ni2 P electrocatalyst synergized with PNC conductive skeleton can efficiently promote chemisorption and catalytic conversion of the electrochemical intermediate lithium polysulfides. In addition, Ni2 P@PNC can effectively decrease the transformation barrier and enhance the precipitation capability for the discharge end-product Li2 S. As a result, the assembled Li–S cells with high sulfur-loading Ni2 P@PNC/S cathode under low electrolyte/sulfur ratio deliver remarkable electrochemical performances in terms of high initial discharge capacity of 1350 mA h g –1, excellent rate capability of 695 mA h g –1 at 2.0 C, as well as outstanding cycle stability with an ultralow capacity decay rate of 0.021% per cycle over 1000 cycles at 2.0 C. Such the inspiring architectonic of multifunctional catalyzing-type sulfur hosts paves a new path for the development of high-performance Li− S batteries.